2014
DOI: 10.1186/1471-2458-14-1076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of female genital mutilation and its effect on women’s health in Bale zone, Ethiopia: a cross-sectional study

Abstract: BackgroundFemales’ genital mutilation (FGM) is one of the harmful traditional practices affecting the health of women and children. It has a long-term physiological, sexual and psychological effect on women. It remains still a serious problem for large proportion of women in most sub-Saharan Africa countries including Ethiopia.MethodsA community based cross sectional study design which is supplemented by qualitative method was conducted in 2014. A total of 634 reproductive age women were involved in the quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
77
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 18 publications
14
77
2
Order By: Relevance
“…and its higher when compared with the study conducted in Mauritania (77%), Gambia (75.6%), Nigeria (50%) and lower than in Egypt (97%). 11,14,15,17,18 It was similar when compared with the study conducted in other countries like Sierra Leone (81.2%), also similar to the findings by Gruenbaum et al, in 2006 in Sudan. 19,20 However, there were many reasons for the persistent practice of (FC) were; to insure virginity, compliance religious instructions, avoid social stigma, good for prospective marriages were significant reason for the practice of (FC) with proportion of (52.2%), (32.9%), (10.2%) and(4.7%), respectively.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…and its higher when compared with the study conducted in Mauritania (77%), Gambia (75.6%), Nigeria (50%) and lower than in Egypt (97%). 11,14,15,17,18 It was similar when compared with the study conducted in other countries like Sierra Leone (81.2%), also similar to the findings by Gruenbaum et al, in 2006 in Sudan. 19,20 However, there were many reasons for the persistent practice of (FC) were; to insure virginity, compliance religious instructions, avoid social stigma, good for prospective marriages were significant reason for the practice of (FC) with proportion of (52.2%), (32.9%), (10.2%) and(4.7%), respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in other study traditional birth attendants, parents, and relatives were the operators. 14,23 However, in the study conducted in rural Gambia all operations were undertaken by traditional operators also similar to the findings by SOAT et al in Sudan who found that more than 60 percent of those performing genital mutilation are traditional midwives. 24 Negative attitudes toward FC could play a significant role in the persistence of this practice in Sudan, in this study the attitude towards female circumcision was generally Negative attitude, i.e.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results were similar to results of Bogale et al, Ibrahim et al and Ibrahim et al Egyptian studies which illustrated that circumcised women were younger at the time of marriage and were mostly from rural areas. 16,22,23 Also, they were found to have a lower level of education with a mean age of FGM at (7.89±4.56), (10.5±1.3), and (9.7±2.1) years old respectively.…”
Section: -21mentioning
confidence: 97%